Comparative analysis of education curricula between germany and indonesia: Content approach and learning methodologies - Pance Mariati; Nadi Suprapto; Neni Mariana; Sunanto Sunanto; Ummu Khairiyah (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2023)
The purpose of this study is to carry out a comparative analysis of the education curriculum between Germany and Indonesia. Considering that Germany and Indonesia have different education systems, this curriculum analysis will be able to add reference sources that can be used as a basis for future curriculum studies. The method in this study uses literature studies from journals, books, and articles related to differences in the education curriculum in Germany and Indonesia. The steps in this study include topic identification, literature search, literature selection, literature evaluation, literature analysis, interpretation of analysis results and article writing. The results of this study are that the educational curriculum in Germany has a distinctive feature that emphasizes the development of practical and professional skills that are relevant to the world of work. Meanwhile in Indonesia, the education curriculum focuses more on mastering academic knowledge and general skills, with an emphasis on developing character and moral values. Learning Methodology in Germany applies a learning approach that is oriented towards practical and interactive experiences, such as project-based learning, simulations and group discussions. Meanwhile in Indonesia, the learning methods used include group discussions, case studies, cooperative learning, and problem-based learning.